Genome-wide analysis of Catalase gene family reveal insights into abiotic stress response mechanism in Brassica juncea and B. rapa - Verma, Deepika (Plant science : an international journal of experimental plant biology, 2023)
Copyright © 2023 Elsevier B.V. All rights reserved.